The Effect Of The Implementation of A Performance-Based Budget on the Accountability Performance of Government Institutions - Ajeng Dwi Ulandari; Tituk Diah Widajantie (Profesional Muda Cendekia Publishing, 2021)
This study aims to examine (1) the effect of budget planning on the performance accountability of OPD Sidoarjo regency government agencies (2) the effect of budget execution on the performance accountability of the Sidoarjo regency OPD government agencies (3) the effect of budget reporting / accountability on the performance accountability of the Sidoarjo regency OPD government agencies. The endogenous variable used is the performance accountability of government agencies. This study used a sample of Sidoarjo Regency Regional Apparatus Organizations, namely 20 Sidoarjo Regency Government Offices. The data collection method is purposive sampling method, by distributing questionnaires. The data analysis technique used Partial Least Square (PLS) with SmartPLS 3.0 software. The results of this study indicate that budget planning and budget reporting / accountability affect the performance accountability of the OPD in Sidoarjo regency government agencies. Meanwhile, budget implementation has no effect on the performance accountability of OPD in Sidoarjo regency government agencies.